2014
DOI: 10.1111/hpb.12150
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant therapy for downstaging of locally advanced hilar cholangiocarcinoma: a systematic review

Abstract: Current evidence suggests that neoadjuvant therapy in patients with unresectable hilar cholangiocarcinoma can be performed safely and in a selected group of patients can lead to subsequent surgical R0 resection. Surgical resection of downstaged patients should be assessed in properly designed phase II studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 35 publications
1
30
0
2
Order By: Relevance
“…No significantly improved OS of these patients was evident regardless of the R0 or R1/2 resection, consistent with results of previous studies [18, 27]. However, other studies have shown a benefit of OS for those patients with positive resection margins (R1/2) or curative resected patients (R0) who received radiation treatment [5, 28]. More studies are warranted to address the optimal radiation dosing and postoperative treatments to improve the outcomes for pCCA patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…No significantly improved OS of these patients was evident regardless of the R0 or R1/2 resection, consistent with results of previous studies [18, 27]. However, other studies have shown a benefit of OS for those patients with positive resection margins (R1/2) or curative resected patients (R0) who received radiation treatment [5, 28]. More studies are warranted to address the optimal radiation dosing and postoperative treatments to improve the outcomes for pCCA patients.…”
Section: Discussionsupporting
confidence: 89%
“…According to the National Cancer Institute's SEER program, the clinical outcomes for patients with perihilar cholangiocarcinoma (pCCA) are poor, with the 5-year survival rate ranging from 25% to 35% for localized cancer to less than 2% for patients with distant metastases [4]. Cholangiocarcinoma is characterized by a poor response to chemotherapy and radiation treatments, and the benefits to these treatments are not yet fully understood [5]. Surgical treatment, especially resections and liver transplantations, are most effective; however, only a few patients are eligible for such treatments because of late diagnoses and the complexity of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…In a cohort of patients undergoing neoadjuvant chemoradiation prior to liver transplantation, 25 % to 42 % patients had complete pathological response in the resected livers [8]. Improved R0 resectability and improved survival has been reported after neoadjuvant chemoradiation for unresectable hilar cholangiocarcinoma [9][10][11]. The Mayo Clinic schedule of neoadjuvant chemoradiation followed by liver transplantation has reported a 5-year survival of 74 % providing evidence of clinical benefit of the pathological response attained with neoadjuvant chemoradiation [12][13][14][15][16][17].…”
Section: Rationale For Use Of Radiation For Cholangiocarcinomamentioning
confidence: 99%
“…For colorectal and pancreatic cancer, several recent reports also demonstrated a clinical advantage with neoadjuvant chemotherapy (18,19). However, the feasibility and efficacy of neoadjuvant chemotherapy for BTC has not been determined (20). Kato et al reported that patients with initially unresectable locally advanced BTC who underwent neoadjuvant chemotherapy (gemcitabine) had a significantly longer survival time compared with those unable to undergo surgery (2-year overall survival rate of 45 and 19%, respectively) (21).…”
Section: Discussionmentioning
confidence: 99%